Simulasi Jaringan MANET Dengan NS3 Untuk Membandingkan Performa Routing Protokol AODV dan DSDV - Nurhayati Jiatmiko; Yudi Prayudi (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2015)
Mobile Ad Hoc Network (MANET) is a wireless LAN technology that does not require a network based infrastructure. MANET is very suitable to be applied in areas experiencing shortages of telecommunications infrastructure. An important aspect in the MANET routing protocol is a protocol which is what set the system routing data packets in the network. MANET itself has many routing protocols to dynamically build the topology. Each of these routing protocols have different characteristics based on how it works. Selection of MANET routing protocols with different types will affect the workings of the delivery and the condition of the network. This paper further research work performance comparison of AODV protocol which is a category on demand and are reactive to update the routing table when the demand and DSDV which is table driven categories that are proactive update its routing table periodically. Comparison AODV protocol and DSDV done in a simulation using the application NS3 (Network Simulator3). Based on the simulation parameters and simulation results for each condition in this research note that AODV suitable for use in scenarios that have a large network density. While DSDV suitable for use in scenarios that have small densityKeywords: MANET, Wireless LAN, Protokol, Routing, AODV, DSDV